2022
DOI: 10.3390/ijerph19127072
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating a Healthy Living Environment for Adolescents in the Post-COVID Era in Hong Kong: Exploring Youth Health Needs

Abstract: Studies have shown that adolescents now have a higher exposure to health risks than those in the past, and Hong Kong adolescents are no exception, particularly with the social crisis in 2019 and then the COVID-19 pandemic in 2020. Data from health care services for children and adolescents only represent the tip of the clinical iceberg, and health profiles, including living habits, lifestyles, data on health status, and health service utilization, are not always readily available for effective planning to cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Furthermore, from the questions asked about the usual practices of coping with stress, it was found that the majority of adolescents had high exposure to electronic devices and social media, which might have been due to the pandemic. Recent studies have argued that excess screen time among youths during the pandemic has resulted in eye discomfort, unhealthy eating habits, family conflicts, concentration difficulties when studying, and even mental health problems ( Rao and Fisher, 2021 ; Ho and Lee, 2022 ). However, in other studies, the use of social media may increase the life satisfaction of some adolescents because it can enhance peer relationships, especially during school closures ( Geraee et al, 2019 ; Orben et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, from the questions asked about the usual practices of coping with stress, it was found that the majority of adolescents had high exposure to electronic devices and social media, which might have been due to the pandemic. Recent studies have argued that excess screen time among youths during the pandemic has resulted in eye discomfort, unhealthy eating habits, family conflicts, concentration difficulties when studying, and even mental health problems ( Rao and Fisher, 2021 ; Ho and Lee, 2022 ). However, in other studies, the use of social media may increase the life satisfaction of some adolescents because it can enhance peer relationships, especially during school closures ( Geraee et al, 2019 ; Orben et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the impact of urbanization on youth mental health in Hong Kong, with mixed results [12,13 ▪▪ ,14 ▪ ,15 ▪▪ ,16 ▪▪ ]. Some studies have found a positive association between urbanization and mental health problems among youth in Hong Kong.…”
Section: Urbanization On Youth Mental Health In Hong Kongmentioning
confidence: 99%
“…The recent COVID-19 pandemic is the typical illustration in affecting the mentality of people. A study conducted among secondary school students in a Hong Kong district revealed a high prevalence of unhealthy behaviors and emotional distress in the post-COVID-19 era [14 ▪ ]. The students exhibited poor sleep quality and quantity, excessive screen time, physical inactivity, and insufficient intake of healthy food.…”
Section: Urbanization On Youth Mental Health In Hong Kongmentioning
confidence: 99%
“…While there have been occasional reports of young people benefitting from the lockdown (Chawla et al, 2021), pandemic-related impacts appear to have been mostly negative. For example, various studies with diverse populations of young people have reported reduced sleep time and quality (Ho & Lee, 2022); heightened emotional distress (including symptoms of post-traumatic stress disorder, anxiety, and depression; Bourion-Bedes et al, 2021; Cielo et al, 2021; Idowu et al, 2020; Islam et al, 2020; Khan et al, 2020; Liang et al, 2020), and significant loneliness (Loades et al, 2020). Losses in learning were also reported, more especially for young people with limited or no access to technology, the internet, or reliable electricity (Giannini, 2020; Van Lancker & Parolin, 2020).…”
Section: Pandemic-related Impacts Reported For Studentsmentioning
confidence: 99%